1972
DOI: 10.2466/pr0.1972.31.3.776
|View full text |Cite
|
Sign up to set email alerts
|

The First Psychiatric Interview: Patients Who Do and Do Not Come

Abstract: 100 patients at a voluntary hospital who kept their first psychiatric appointments were compared on 31 variables with 100 patients who did not. Patients whose problems had become more acute prior to their appointment and those who mentioned some expectation of what was going to happen to them were more likely to have kept the appointments. The findings suggest the need for facilities where there is no waiting and also indicate the importance of quickly educating potential psychiatric patients about the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In direct contrast to these studies are the findings that children referred for developmental problems (Ross & Lacey, 1961) and externalizing behaviors, such as conduct disorder, oppositional defiant disorder, and attention deficit disorder (Viale, Rosenthal, Curtiss, & Marohn, 1984), were more likely to remain in treatment than to drop out. Another study (Gottesfeld & Martinez, 1972) looked at the acuteness of the described problem but was unable to report any conclusive findings.…”
Section: Factors Associated With Nonattendancementioning
confidence: 98%
“…In direct contrast to these studies are the findings that children referred for developmental problems (Ross & Lacey, 1961) and externalizing behaviors, such as conduct disorder, oppositional defiant disorder, and attention deficit disorder (Viale, Rosenthal, Curtiss, & Marohn, 1984), were more likely to remain in treatment than to drop out. Another study (Gottesfeld & Martinez, 1972) looked at the acuteness of the described problem but was unable to report any conclusive findings.…”
Section: Factors Associated With Nonattendancementioning
confidence: 98%
“…Although attendance in the initial session (intake) has been reported as high as 85% (Noonan, 1973), most studies have indicated less favorable results. In fact, when mental health services fail to implement interventions that are specifically designed to improve attendance, only 22 to 70% (usually about 50%) of patients have been found to attend their first scheduled session (Allan, 1988;Burgoyne, Acosta, & Yamamoto, 1990;Campbell, Scilagyi, Rodewald, Doane, & Roghmann, 1994;Gottesfeld & Martinez, 1972;Hershorn & Rivas, 1993;Hochstadt & Trybula, 1980;Kourany, Garber, & Tornusciolo, 1990;Levy & Claravall, 1977;McKernan, McKay, McCadam, & Gonzalez, 1996;Nazarian, Mechaber, Charney, & Coulter, 1974;Overall & Aronson, 1963;Parrish, Charlop, & Fenton, 1984;Raynes & Warren, 1971;Rosenberg & Raynes, 1973;Ross, Friman, & Christopherson, 1993;Shepard & Moseley, 1976;Smith, Wienman, & Wait, 1990;Swenson & Pakarik, 1988;Tantum & Klerman, 1979;Turner & Vernon, 1976;Webster, 1992). Initial session attendance in substance abuse clinics is also about 50% (Gariti et al, 1995), and substance abuse, young age, and antisocial behavior have all been found to be associated with missed appointments (Cohen & Richardson, 1970;Deyo & Inui, 1980;Matas, Staley, & Griffin, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Raynes & W arren (1971) noted that the client group was largely working class which could account for the low attendance rate, but this was not a variable they examined. Gottesfeld & Martinez (1972) examined a long list of clinical and demographic variables in an attempt to distinguish attenders (n=100) from non-attenders (n=31) at a psychiatric hospital out-patient clinic. Every client in the study was interviewed in person at hom e. No differences between attenders and non-attenders emerged except on two variables: clients whose problems had become m ore acute prior to their appointment and clients who had som e idea of what to expect were m ore likely to attend.…”
Section: Characteristics Of Non-attendersmentioning
confidence: 99%